Bucklandia dichotoma SP. NOV. DEL ]URÁSICO MEDIO DE RAJMAHAL HILLS, INDIA (Ameghiniana, 2013)
The present paper deals with the description of a dichotomously branched specimen of Bucklandia, B. dichotoma sp. nov. collected from the Rajmahal Hills, India. The present stem possesses an assemblage of peculiar anatomical characters and thus the author has compared it with al! the possible allied groups of plants like, Bennettitales, Cycadeoidales and vesseless Magnoliales. Study of this new species has certainly proved useful in correlating Bucklandias with the primitive Angiospermous plants.